Secondary battery and preparation method thereof
By combining the second organic solvent in the positive electrode sheet of the lithium-ion battery, the problem of solvent removal when preparing the positive electrode slurry in the prior art is solved, the effect of simplifying the process flow and reducing costs is achieved, and the cycle performance and safety performance of the battery are improved.
Patent Information
- Application Number
- CN202510207802.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing lithium-ion batteries need to remove solvents when preparing the positive electrode slurry, which increases manufacturing cost and energy consumption; at the same time, the difference in battery liquid injection volume affects circulation and safety performance.
Using a secondary battery and its preparation method, by combining the second organic solvent in the positive electrode active material layer of the positive electrode sheet, it does not need to remove the second organic solvent as part of the organic solvent in the electrolyte solution, simplifying the process flow and reducing costs.
It reduces battery manufacturing costs and energy consumption, improves production efficiency, ensures battery uniformity and stability, and improves cycle performance and safety performance.
Smart Images

Figure CN119725685A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery preparation, and in particular to a secondary battery and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have the characteristics of high operating voltage, high energy density and excellent cycle performance. Their performance optimization and cost control have become the focus of research and development. Existing lithium-ion batteries include the preparation of positive electrode slurry. The common processes for preparing positive electrode slurry are dry process and wet process. Among them, the wet process requires a large amount of solvent for stirring and dispersion, and then the solvent needs to be removed by drying during the coating process. This process not only consumes a lot of energy, but also increases the manufacturing cost. The dry process is to first mix the positive electrode main material, conductive agent and binder dry powder, but the agglomeration phenomenon of these dry powders is serious. It is difficult to achieve the ideal dispersion effect by direct mixing, which affects the uniformity of the slurry and reduces the coating effect of the electrode. At the same time, the coating preparation of the electrode also needs to be dried to remove the solvent.
[0003] The amount of liquid injected during the battery production process will directly affect the battery's electrical performance and safety performance. When the amount of liquid injected is too small, it will cause abnormal phenomena such as insufficient internal battery reaction, lithium deposition in the negative electrode of the battery, low battery capacity and poor cycle retention rate; when the amount of liquid injected is large, it will not only cause electrolyte waste and increase battery manufacturing costs, but it is also likely to cause abnormalities such as large gas production during battery formation, poor battery appearance, and deterioration of electrochemical properties and safety. Although there are injection coefficients for batteries with different main material systems in the industry as reference standards for battery injection volume, if different positive main materials are used, different injection coefficients are calculated, but even if the same batch of positive main materials are used in the battery preparation process, due to differences in the preparation process, the content of positive active materials contained in different pole cores is different, and the corresponding amount of electrolyte injected into the pole core is different, which will cause a large difference between the actual battery injection volume and the theoretical value, affecting the battery's cycle performance and safety performance. Summary of the invention
[0004] In view of the problem that the existing wet or dry processes for preparing positive electrode slurry require the removal of solvents, which increases manufacturing costs, and there is a large difference between the actual battery injection volume and the theoretical value, which affects the battery cycle performance, the present application provides a secondary battery and a preparation method thereof.
[0005] In one aspect, the present invention provides a secondary battery, comprising a core and a shell, wherein the core and an electrolyte are arranged in the shell, the core comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer is obtained by compounding a positive electrode mass material on at least one side of the surface of the positive electrode current collector; The electrolyte includes an organic solvent, the organic solvent includes a first organic solvent and a second organic solvent, the positive electrode active material layer includes a solid powder and the second organic solvent, and the solid powder includes a positive electrode active material; The mass Me of the electrolyte actually injected into the shell satisfies the relation 1: Relation 1; Wherein, Mc is the mass of the positive electrode active material in the positive electrode active material layer, in g; S is the mass proportion of the positive electrode active material in the solid powder, unit: %; C is the theoretical gram capacity of the positive electrode active material, in Ah / g; Y is the filling coefficient of the battery, in g / Ah; N is the mass proportion of the first organic solvent in the organic solvent; X is the solid content of the positive electrode pellet material, in %.
[0006] Preferably, S is 94% to 98%; And / or, Y is 2.5~5g / Ah.
[0007] Preferably, N is 70% to 90%; And / or, X ≥ 70%.
[0008] Preferably, C is 0.07~0.3Ah / g.
[0009] Preferably, the positive electrode active material includes at least one of a lithium-containing compound and a sodium-containing compound; The lithium-containing compound includes one or more of lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel cobalt manganese oxide, and lithium-rich manganese-based materials; The sodium-containing compound includes one or more of Prussian blue compounds, sodium transition metal oxides and polyanion compounds; The second organic solvent includes one or more of a carbonate solvent and ethyl acetate; The carbonate solvent includes one or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, vinylene carbonate, and fluoroethylene carbonate; The first organic solvent includes one or more of nitrile solvents, carboxylate solvents, ether solvents, and carbonate solvents.
[0010] In a second aspect, the present application provides a method for preparing the secondary battery described above, comprising the following steps: Obtaining the positive electrode sheet, the negative electrode sheet and the separator, and assembling the positive electrode sheet, the separator and the negative electrode sheet into a pole core; Placing the pole core in a shell, injecting electrolyte into the shell, and performing formation to obtain the battery; The mass Me of the injected electrolyte satisfies the relation 1: Relationship 1.
[0011] Preferably, obtaining the positive electrode sheet comprises the following steps: Prepare a positive electrode mass material, and compound the positive electrode mass material onto at least one side surface of the positive electrode current collector, The method for preparing the positive electrode mass material comprises the following steps: The positive electrode active material and the positive electrode conductive agent are mixed evenly to obtain a dry powder precursor; Mixing the positive electrode binder and the second organic solvent uniformly to obtain a glue solution; The dry powder precursor is mixed with the glue solution to obtain the positive electrode mass material; The solid content X of the positive electrode mass material is ≥75%.
[0012] Preferably, the positive electrode conductive agent includes one or more of carbon black, acetylene black, Ketjen black, graphene microspheres, three-dimensional conductive metal organic frameworks, porous spherical carbon, conductive nanotubes, nanofibers, graphene, and graphite microsheets; And / or, the positive electrode binder includes one or more of polytetrafluoroethylene and its modified polymers, rubber, modified rubber, polyvinylidene fluoride, modified polyvinylidene fluoride, polyimide, modified polyimide, polypropylene, modified polypropylene, polyacrylic acid, modified polyacrylic acid, polyvinyl alcohol, modified polyvinyl alcohol, polyvinyl butyral, modified polyvinyl butyral and polyacrylonitrile and modified polyacrylonitrile.
[0013] Preferably, compounding the positive electrode mass material onto at least one side surface of the positive electrode current collector comprises the following steps: The positive electrode mass material is prepared by rolling or rolling to obtain a positive electrode active material layer, and the positive electrode active material layer is compounded with at least one side surface of the positive electrode current collector to obtain the positive electrode sheet.
[0014] Preferably, the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder is (94-98): (1-3): (1-3); And / or, in the glue solution, the mass ratio of the positive electrode binder to the second organic solvent is (1-3): (30-40).
[0015] The secondary battery provided by the present application, the electrolyte includes an organic solvent, the organic solvent includes a first organic solvent and a second organic solvent, the positive electrode active material layer includes the second solvent, the second organic solvent is a part of the organic solvent in the electrolyte, and the second organic solvent in the positive electrode active material layer does not need to be removed during the battery preparation process, thereby avoiding subsequent drying of the positive electrode sheet and solvent recovery, greatly reducing the manufacturing cost of the battery, reducing energy consumption, shortening the process flow, and improving production efficiency. In the battery provided by the present application, the mass Me of the electrolyte actually injected into the shell satisfies the relationship 1: , which has the following effects: 1) Since the positive active material layer of the positive electrode sheet itself contains the second organic solvent, the amount of electrolyte absorbed during the injection process is reduced, shortening the injection time. 2) The mass Me of the injected electrolyte satisfies the relationship 1. Me is related to Mc, X, and S. Mc is related to the mass of the positive active material contained in the actual positive electrode sheet of the corresponding electrode core. It can avoid the problem of large differences between the actual injection amount of the battery and the theoretical value due to the different contents of the actual positive active materials contained in the preparation process of different electrode cores, and ensure that each electrode core can be injected with an appropriate amount of electrolyte according to the actual amount of positive active material contained, reducing the difference between the actual injection amount of the battery and the theoretical value, improving the uniformity and stability of the battery, and improving the cycle performance of the battery. 3) The obtained battery electrolyte has good infiltration of the electrode sheet, and the electrolyte has high ion conductivity, which improves the rate performance of the battery and reduces the battery impedance. 4) The mass Me of the electrolyte injected into the battery satisfies equation 1, and the battery volume will not increase. The battery has high volume energy density and mass energy density, which also prevents battery leakage, improves battery safety performance, and reduces battery manufacturing costs. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0017] In order to illustrate the technical solution of the present invention, specific embodiments are provided below for illustration.
[0018] On the one hand, the present application provides a secondary battery, comprising a pole core and a shell, wherein the pole core and an electrolyte are arranged in the shell, the pole core comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer is obtained by compounding a positive electrode mass material on at least one side of the surface of the positive electrode current collector; The electrolyte includes an organic solvent, the organic solvent includes a first organic solvent and a second organic solvent, the positive electrode active material layer includes a solid powder and the second organic solvent, and the solid powder includes a positive electrode active material; The mass Me of the electrolyte actually injected into the shell satisfies the relation 1: Relation 1; Wherein, Mc is the mass of the positive electrode active material in the positive electrode active material layer, in g; S is the mass proportion of the positive electrode active material in the solid powder, unit: %; C is the theoretical gram capacity of the positive electrode active material, in mAh / g; Y is the filling coefficient of the battery; N is the mass proportion of the first organic solvent in the organic solvent; X is the solid content of the positive electrode pellet material, in %.
[0019] Specifically, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer is obtained by compounding a positive electrode mass material on at least one side of the surface of the positive electrode current collector. The positive electrode active material layer includes a solid powder and a second organic solvent, and the positive electrode mass material is obtained by mixing the second organic solvent with the solid powder. The second organic solvent is a part of the organic solvent in the electrolyte, so the second organic solvent does not need to be removed during the battery preparation process, avoiding the subsequent drying of the positive electrode sheet and the recovery of the second organic solvent, greatly reducing the manufacturing cost of the battery, reducing energy consumption, shortening the process flow, and improving production efficiency.
[0020] The shell may be made of metal, alloy, plastic or aluminum-plastic film. For example, the shell may be an aluminum shell, a steel shell, a plastic shell or an aluminum-plastic film.
[0021] The shell contains a core and an electrolyte. The positive electrode active material layer of the positive electrode sheet contains a second organic solvent. Since the second organic solvent is a part of the organic solvent in the electrolyte, the second organic solvent in the positive electrode active material layer does not need to be removed. In the battery injection process, the mass Me of the injected electrolyte satisfies the relationship 1, Equation 1 has the following effects: 1) Since the positive active material layer of the positive electrode sheet itself contains the second organic solvent, which is part of the organic solvent in the electrolyte, the amount of electrolyte absorbed during the injection process is small, shortening the injection time. 2) The mass Me of the injected electrolyte satisfies equation 1. Me is related to Mc, X, and S. Me is related to the mass of the positive active material contained in the actual positive electrode sheet of the corresponding electrode core. It can avoid the problem of large differences between the actual injection amount of the battery and the theoretical value due to the different contents of the actual positive active materials contained in the preparation process of different electrode cores, and ensure that each electrode core can be injected with an appropriate amount of electrolyte according to the actual amount of positive active material contained, reducing the difference between the actual injection amount of the battery and the theoretical value, improving the uniformity and stability of the battery, and improving the cycle performance of the battery. 3) The obtained battery electrolyte has good infiltration of the electrode sheet, and the electrolyte has high ion conductivity, which improves the rate performance of the battery and reduces the battery impedance. 4) The injection mass Me of the electrolyte in the battery satisfies equation 1, and the battery volume will not increase. The battery has high volume energy density and mass energy density, which also avoids battery leakage, improves battery safety performance, and reduces battery manufacturing costs.
[0022] If Me is less than The amount of electrolyte injected into the battery is too low, the electrolyte infiltration into the positive and negative electrode sheets becomes worse, the wettability of the electrode sheets becomes worse, the electrolyte content is low, and the electrolyte ion conductivity is reduced during the battery charge and discharge process. The battery cycle performance and rate performance are reduced, the concentration polarization inside the battery increases, and the battery impedance increases.
[0023] If Me is greater than , the electrolyte content is too high. Too much electrolyte is injected into the battery, the volume of the battery becomes larger, and the battery volume energy density and mass energy density decrease. Due to the large amount of electrolyte injected, safety problems such as leakage may occur, increasing the manufacturing cost of the battery; the battery impedance increases, affecting the electrical performance of the battery.
[0024] In some embodiments, S is 94% to 98%.
[0025] Specifically, S is the mass ratio of the positive electrode active material in the solid powder, that is, in all the dry powders of the positive electrode agglomerate material, the mass ratio of the positive electrode active material is 0.94~0.98, and the content of the positive electrode active material is high, ensuring that the battery has a high capacity. Specifically, the specific value of S can be 94%, 945%, 95%, 955%, 96%, 965%, 97%, 975%, 98%, etc., as long as S is within the range of 94%~98%.
[0026] In some embodiments, Y is 2.5-5 g / Ah.
[0027] Specifically, Y is the injection coefficient of the battery. The unit of Y is g / Ah. The injection coefficient Y refers to the mass (g) of electrolyte that needs to be injected into the battery per ampere-hour (Ah) capacity. Using different types of positive electrode active materials, the corresponding gram capacity is also different, and the capacity of the resulting battery is also different. The injection coefficient of the positive electrode active material used in the secondary battery is in the range of 2.5~5g / Ah, which can ensure that the battery has sufficient electrolyte to support the electrochemical reaction and ensure that the electrolyte continues to well infiltrate the positive electrode active material during the battery cycle. Specifically, the value of Y can be 2.5g / Ah, 3.0g / Ah, 3.5g / Ah, 4.0g / Ah, 4.5g / Ah, 5.0g / Ah, etc., as long as the value of Y is in the range of 2.5~5g / Ah.
[0028] In some preferred embodiments, Y is 3-5 g / Ah.
[0029] When Y is in the range of 3-5 g / Ah, the electrolyte content in the battery is appropriate, the obtained battery electrolyte has good infiltration of the electrode, the electrolyte has high ion conductivity, the battery rate performance is improved, and the battery impedance is reduced.
[0030] In some embodiments, N is 70% to 90%.
[0031] Specifically, N is the mass ratio of the first organic solvent in the organic solvent. In the electrolyte, it includes electrolytes, additives and organic solvents, the organic solvent includes a first organic solvent and a second organic solvent, N is the mass ratio of the second organic solvent in the organic solvent in the electrolyte, the first organic solvent is directly added to the electrolyte, and the second organic solvent is used as a solvent for the slurry when preparing the positive electrode mass material.
[0032] The secondary battery provided by the present application contains a second organic solvent in the positive electrode active material layer. The second organic can be used as a part of the organic solvent in the electrolyte, so the solvent in the electrolyte is reduced. Compared with the existing batteries, the amount of injected electrolyte is relatively reduced, the time for the battery to absorb the electrolyte is reduced, the process time is shortened, and the production efficiency is improved.
[0033] The value of N can be 70%, 75%, 80%, 82%, 84%, 85%, 87%, 89%, 90%, etc., as long as N is within the range of 80~90%.
[0034] In some preferred embodiments, N is 80% to 90%.
[0035] When N is in the range of 80% to 90%, the content of electrolyte injected into the battery is high, the injection time is shortened, the electrolyte injected into the battery can better infiltrate the electrode, the ion conductivity of the electrolyte is improved, and the battery electrical performance is improved.
[0036] In some embodiments, X ≥ 70%.
[0037] Specifically, the solvent used in the positive electrode mass material is a second organic solvent. The second organic solvent is part of the organic solvent in the electrolyte. The second organic solvent in the positive electrode mass material does not need to be removed, and the solid content of the positive electrode mass material can be increased. The present application limits the solid content X of the positive electrode mass material to ≥70%. The solid content of the positive electrode mass material is relatively high, and no coating process is required when preparing the positive electrode sheet. The positive electrode mass material is first rolled or rolled into a thin sheet (that is, a positive electrode active material layer) through a composite process, and then the thin sheet is composited with the surface of the positive electrode collector to obtain a positive electrode sheet. Since an oven does not need to be used for heating when preparing the positive electrode sheet, the preparation cost is reduced and the energy consumption is reduced. Compared with the existing low-solid-content positive electrode mass material, the positive electrode mass material of the present application has a higher solid content, which can effectively improve the energy density of the battery.
[0038] Preferably, X is ≥ 75%. The solid content of the positive electrode agglomerated material is ≥ 75%, and the positive electrode active material contained therein has a high solid content, which reduces production costs and effectively improves battery energy density.
[0039] In some embodiments, C is 0.07-0.3 Ah / g.
[0040] Specifically, C is the theoretical gram capacity of the positive electrode active material. Different types of positive electrode active materials have corresponding theoretical gram capacities. For example, when the positive electrode active material is lithium iron phosphate, its theoretical gram capacity is 170 mAh / g.
[0041] In some embodiments, the positive electrode active material includes at least one of a lithium-containing compound and a sodium-containing compound; the lithium-containing compound includes one or more of lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel cobalt manganese oxide, and lithium-rich manganese-based materials; The sodium-containing compound includes one or more of Prussian blue compounds, sodium transition metal oxides and polyanion compounds.
[0042] Lithium nickel cobalt manganese oxide is a common ternary material with the chemical formula LiNi x Co y Mn 1-x-y O 2 , 0<x<1, 0<y<1.
[0043] Lithium-rich manganese-based materials are a type of material with lithium and manganese as the main components. 2 MnO 3 Based on LiMO 2 (M is usually Ni, Co, Mn or a combination thereof) to form a composite positive electrode material.
[0044] In some embodiments, the Prussian blue compound may be a compound having sodium ions, transition metal ions and cyanide ions (CN - The transition metal may be one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. Non-limiting examples of Prussian blue compounds may be Na a Me b Me' c( CN) 6 , wherein Me and Me' can each independently be one or more of Ni, Cu, Fe, Mn, Co and Zn, <a≤2,0<b<1,0<c<1。
[0045] In some embodiments, the polyanion compound can also be a compound having sodium ions, transition metal ions, tetrahedral (YO 4 ) n- The transition metal herein may be one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y may be one or more of P, S and Si, and n represents (YO 4 ) n- valence state; the halogen may be one or more of F, Cl and Br.
[0046] In some embodiments, the polyanionic compound may also be a compound having sodium ions, tetrahedral (YO 4 ) n- Anion unit, polyhedral unit (ZO y ) m+ and an optional halogen anion. Y can be one or more of P, S and Si, and n represents (YO 4 ) n- valence state; Z represents a transition metal, which may be one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; m represents (ZO y ) m+ valence state; the halogen may be one or more of F, Cl and Br.
[0047] In some embodiments, the polyanion compound may be NaFePO 4 、Na 3 V 2 (PO 4 ) 3 、NaM'PO 4 F and Na 3 (VO y ) 2(PO 4 ) 2 F 3-2y (0≤y≤1) or more; wherein NaM'PO 4 M' in F may include one or more of V, Fe, Mn and Ni.
[0048] In some embodiments, the sodium transition metal oxide may be Na 1-x Cu h Fe k Mn l M 1 m O 2-y , where M 1 It may be one or more of Li, Be, B, Mg, Al, K, Ca, Ti, Co, Ni, Zn, Ga, Sr, Y, Nb, Mo, In, Sn and Ba. <x≤0.33,0<h≤0.24,0≤k≤0.32,0<l≤0.68,0≤m<0.1,h+k+l+m=1,0≤y<0.2。
[0049] In some embodiments, the second organic solvent includes one or more of a carbonate solvent and ethyl acetate.
[0050] Specifically, the second organic solvent used in the preparation of the positive electrode lump material is a part of the organic solvent in the electrolyte. The second organic solvent includes one or more of carbonate solvents and ethyl acetate, which can be evenly mixed with the positive electrode active material, positive electrode conductor, and positive electrode binder to obtain a uniform and stable positive electrode lump material.
[0051] In some embodiments, the carbonate solvent includes one or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, vinylene carbonate, and fluoroethylene carbonate.
[0052] Carbonate solvents include the above-mentioned types, which are conducive to uniform mixing with the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder.
[0053] In some embodiments, the first organic solvent includes one or more of a nitrile solvent, a carboxylate solvent, an ether solvent, and a carbonate solvent. Nitrile solvents may be, for example, acetonitrile, malononitrile, glutaronitrile, and the like. Ether solvents include 1,3-dioxolane, 1,4-dioxane, tetrahydrofuran, 2-methyltetrahydrofuran, 2-trifluoromethyltetrahydrofuran, and the like. Carbonate solvents include one or more of ethylene carbonate (EC), propylene carbonate (PC), γ-butyrolactone (GBL), butylene carbonate (BC), vinylene carbonate, dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dipropyl carbonate (DPC).
[0054] The electrolyte of the present application is an electrolyte commonly used in existing lithium-ion batteries, or an electrolyte commonly used in sodium-ion batteries, and the present application does not make any limitation.
[0055] In a second aspect, the present application provides a method for preparing a secondary battery, comprising the following steps: Obtaining the positive electrode sheet, the negative electrode sheet and the separator, and assembling the positive electrode sheet, the separator and the negative electrode sheet into a pole core; Placing the pole core in a shell, injecting electrolyte into the shell, and performing formation to obtain the battery; The mass Me of the injected electrolyte satisfies the relation 1: Relationship 1.
[0056] In the preparation method of the secondary battery provided in the present application, the positive electrode active material layer of the positive electrode sheet includes a second organic solvent, and the second organic solvent can be used as a part of the organic solvent in the electrolyte, and there is no need to remove the second organic solvent. Therefore, the mass Me of the electrolyte injected in the injection process of the battery preparation needs to satisfy the relationship 1: , reducing the step of removing the second organic solvent from the positive electrode sheet, reducing the use and recovery of the second organic solvent, reducing production costs, simplifying the production process, reducing energy consumption, and improving battery production efficiency.
[0057] In some embodiments, obtaining the positive electrode sheet comprises the following steps: Prepare a positive electrode mass material, and compound the positive electrode mass material onto at least one side surface of the positive electrode current collector, The method for preparing the positive electrode mass material comprises the following steps: The positive electrode active material and the positive electrode conductive agent are mixed evenly to obtain a dry powder precursor; Mixing the positive electrode binder and the second organic solvent uniformly to obtain a glue solution; The dry powder precursor is mixed with the glue solution to obtain the positive electrode mass material; The solid content X of the positive electrode mass material is ≥70%.
[0058] Specifically, the solvent used to prepare the positive electrode mass material is a second organic solvent, which is a part of the organic solvent of the electrolyte. It is not necessary to remove the second organic solvent, which avoids the subsequent drying of the pole piece and the recovery process of the second organic solvent. No coating is required, so the solid content of the positive electrode mass material can be relatively high. The present application limits the solid content X of the positive electrode mass material to ≥ 70%. Due to the high solid content, in the process of preparing the positive electrode mass material, a dry powder precursor and a glue are first prepared. The preparation of the dry powder precursor is conducive to mixing the positive active material and the positive conductive agent evenly, and then the glue and the dry powder precursor are mixed, which is conducive to mixing the glue and the dry powder precursor evenly to obtain a uniform and stable positive electrode mass material. The solid content X of the positive electrode mass material can be 70%, 75%, 80%, 85%, etc., as long as the solid content X is greater than or equal to 70%.
[0059] It should be noted that the uniform mixing method may be any one of planetary mixing, twin-screw mixing, and dry kneading.
[0060] In some embodiments, the positive electrode conductive agent includes one or more of carbon black, acetylene black, Ketjen black, graphene microspheres, three-dimensional conductive metal organic frameworks, porous spherical carbon, conductive nanotubes, nanofibers, graphene, and graphite microsheets; And / or, the positive electrode binder includes one or more of polytetrafluoroethylene and its modified polymers, rubber, modified rubber, polyvinylidene fluoride, modified polyvinylidene fluoride, polyimide, modified polyimide, polypropylene, modified polypropylene, polyacrylic acid, modified polyacrylic acid, polyvinyl alcohol, modified polyvinyl alcohol, polyvinyl butyral, modified polyvinyl butyral and polyacrylonitrile and modified polyacrylonitrile.
[0061] In some embodiments, compounding the positive electrode mass material onto at least one side surface of the positive electrode current collector comprises the following steps: The positive electrode mass material is prepared by rolling or rolling to obtain a positive electrode active material layer, and the positive electrode active material layer is compounded with at least one side surface of the positive electrode current collector to obtain the positive electrode sheet.
[0062] Specifically, because the solid content of the positive electrode agglomerate material is greater than or equal to 70%, and the solid content of the slurry is relatively high, the positive electrode agglomerate material is rolled or rolled to prepare a thin sheet, which is the positive electrode active material layer, and then the positive electrode active material layer is compounded with at least one side of the positive electrode current collector to obtain a positive electrode sheet. In the preparation of the positive electrode sheet provided by the present application, the solid content of the positive electrode agglomerate material is greater than or equal to 70%, the solid content is relatively high, and a coating process is not required, which reduces the drying of the electrode sheet and the recovery process of the second organic solvent, and reduces the manufacturing cost and energy consumption.
[0063] It should be noted that, in order to facilitate the preparation of thin sheets, the slurry can be first kneaded into a mass, and then a double-roll mill is used to decompress the mass into a thin sheet, thereby facilitating the composite of the thin sheet and the current collector.
[0064] In some embodiments, the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder is (94~98): (1~3): (1~3).
[0065] Specifically, the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder is in the range of (94~98):(1~3):(1~3), which can ensure that the battery has sufficient active materials to participate in the electrochemical reaction of the battery and improve the energy density of the battery; at the same time, it makes the battery impedance low and improves the charging and discharging efficiency of the battery.
[0066] More preferably, the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder is (95-98): (1.5-2.5): (1.0-3).
[0067] In some embodiments, in the glue solution, the mass ratio of the positive electrode binder to the second organic solvent is (1-3): (30-40).
[0068] Specifically, the positive electrode binder and the second organic solvent are evenly mixed to prepare a glue solution, wherein the mass ratio of the positive electrode binder to the second organic solvent is in the range of (1-3): (30-40), which is conducive to mixing the second organic solvent and the binder to form a uniform and stable glue solution.
[0069] The mass ratio of the positive electrode binder to the second organic solvent can be 1:30, 1:35, 1:40, 2:34, 2:38, 2.5:33, 2.5:36, 2.5:40, etc., as long as the mass ratio of the positive electrode binder to the second organic solvent is within the range of (1~3): (30~40).
[0070] It should be noted that the method for obtaining the negative electrode sheet can adopt the existing technology, and this application does not limit it.
[0071] In some embodiments, obtaining the negative electrode sheet comprises the following steps: The negative electrode active material, negative electrode conductive agent, thickener and negative electrode binder are uniformly mixed to obtain negative electrode slurry, and the negative electrode slurry is coated on at least one side of the surface of the negative electrode current collector, and dried and rolled to obtain a negative electrode sheet.
[0072] The negative electrode active material includes at least one of carbon material, silicon material and silicon-carbon material. The carbon material includes at least one of artificial graphite, natural graphite, hard carbon, mesophase micro carbon beads and soft carbon.
[0073] The negative electrode conductive agent includes at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0074] The negative electrode binder includes at least one of polyacrylic acid, sodium polyacrylate, polyvinyl alcohol, styrene-butadiene rubber, sodium alginate, polymethacrylic acid and carboxymethyl chitosan.
[0075] The thickener includes at least one of sodium carboxymethyl cellulose.
[0076] The mass ratio of the negative electrode active material, the negative electrode conductive agent, the thickener and the negative electrode binder is (94~97): (1~2): (1~2): (1~2).
[0077] The mass ratio of the negative electrode active material, the negative electrode conductive agent, the thickener and the negative electrode binder can be adjusted within the range of (94~97):(1~2):(1~2):(1~2), such as the mass ratio of the negative electrode active material, the negative electrode conductive agent, the negative electrode dispersant and the negative electrode binder can be 94:1:1.5:1.2, etc.
[0078] The secondary battery provided by the present application includes at least one of a sodium ion battery and a lithium ion battery. If the secondary battery is a sodium ion battery, the selected positive electrode active material is a compound containing the sodium element, and the electrolyte used in the existing sodium ion battery, the raw materials used in the negative electrode sheet, etc. are selected, and the sodium ion battery is prepared according to the above-mentioned secondary battery preparation process. If the battery is a lithium ion battery, the selected positive electrode active material is a compound containing the lithium element, and the electrolyte used in the existing lithium ion battery, the raw materials used in the negative electrode sheet, etc. are selected, and the lithium ion battery is prepared according to the above-mentioned secondary battery preparation process.
[0079] The present invention is further described below by way of examples.
[0080] Example 1 A 1.2Ah lithium-ion battery was prepared, and the preparation method was as follows.
[0081] S1: Preparation of positive electrode pellets S11: preparing glue solution: heating to melt the second organic solvent propylene carbonate, adding polyvinylidene fluoride and mixing thoroughly to form glue solution, wherein the mass ratio of polyvinylidene fluoride to propylene carbonate is 2:32.
[0082] S12: Prepare dry powder precursor: put lithium iron phosphate and carbon black in a beaker, place on a heating table at high temperature and stir and mix thoroughly to obtain dry powder precursor. The theoretical gram capacity C of lithium iron phosphate is 0.17Ah / g.
[0083] S13: Slowly pour the glue obtained in step S11 into a beaker in batches, and mix it evenly with the dry powder precursor obtained in step S12 to obtain a positive electrode agglomerate material. The mass ratio of lithium iron phosphate, carbon black, and polyvinylidene fluoride is 97:2:2, and S is 96.04%. The solid content X of the prepared positive electrode agglomerate material is 75.9%.
[0084] S2: Preparation of positive electrode S21: kneading ingredients: kneading the positive electrode mass material obtained in step S13 into a uniform mass by using a kneading method; Rolling and laminating: Using a heated roller machine, roll the mass to obtain a thin sheet, and then laminate the thin sheet with the two sides of the positive electrode current collector aluminum foil to form a positive electrode sheet, and cool it to room temperature to set its shape. The prepared positive electrode sheet has a Mc of 5g.
[0085] S3: Preparation of negative electrode sheet Graphite, carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 94:2:2:2, deionized water is added and mixed evenly to obtain a negative electrode slurry, the negative electrode slurry is coated on both sides of a copper foil, and the negative electrode sheets are obtained by drying, rolling and slitting.
[0086] S4: Preparation of lithium-ion batteries The positive electrode sheet obtained in step S2, the negative electrode sheet obtained in step S3, and the separator are assembled into a pole core through a winding process, and the pole core is placed in a shell, and an electrolyte is injected into the shell. The shell is immersed at a high temperature of 45°C for 48 hours, and then the battery is formed; the battery injection coefficient Y is 3.2g / Ah.
[0087] The electrolyte includes a first organic solvent, an electrolyte salt and a film-forming additive, and the specific contents are as follows: the first organic solvent is ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC), and the mass ratio of EC:EMC:DMC is 30:30:40. The mass content of lithium hexafluorophosphate in the electrolyte is 13%; the film-forming additives in the electrolyte are VC and FEC, wherein the mass content of vinylene carbonate (VC) in the electrolyte is 2%, and the mass content of fluoroethylene carbonate (FEC) in the electrolyte is 0.5%.
[0088] The electrolyte includes an organic solvent, and the organic solvent includes the first organic solvent in step S11 and the second organic solvent in step S4. The mass proportion N of the first organic solvent in the organic solvent is 84%.
[0089] The mass Me of the injected electrolyte satisfies the relationship 1: ; The specific values of Mc, S, C, Y, N, and X are shown in Table 1.
[0090] Example 2 The steps of this embodiment are similar to those of Embodiment 1, except that in step S11, the mass ratio of polyvinylidene fluoride to propylene carbonate is 1:30; in step S13, the mass ratio of lithium iron phosphate, carbon black, and polyvinylidene fluoride is 98:1:1; the rest are the same as in Embodiment 1.
[0091] Example 3 The steps of this embodiment are similar to those of Embodiment 1, except that in step S11, the mass ratio of polyvinylidene fluoride to propylene carbonate is 3:32; in step S13, the mass ratio of lithium iron phosphate, carbon black, and polyvinylidene fluoride is 94:3:3; the rest are the same as in Embodiment 1.
[0092] Embodiment 4-6 The steps of Examples 4 to 6 are similar to those of Example 1, except that the Me values are different, and the rest are the same as Example 1.
[0093] Example 7 The steps of Example 7 are similar to those of Example 1, except that the type of positive electrode active material is different, Me is different, the positive electrode active material in Example 7 is lithium manganese oxide, and C is 0.148 Ah / g. The rest is the same as Example 1.
[0094] Example 8 The steps of Example 8 and Example 1 are similar, except that the type of positive electrode active material is different, Me is different, the positive electrode active material in Example 8 is lithium nickel cobalt manganese oxide NMC, and C is 0.280 Ah / g. The rest is the same as Example 1.
[0095] Example 9 The steps of Example 9 are similar to those of Example 1, except that the type of the second organic solvent in step S11 is different, namely, dimethyl carbonate. The rest is the same as that of Example 1.
[0096] Example 10 The steps of Example 10 are similar to those of Example 1, except that the type of the second organic solvent in step S11 is different, namely, ethyl methyl carbonate. The rest is the same as that of Example 1.
[0097] Comparative Example 1~2 The major steps of Comparative Examples 1-2 are the same as those of Example 1, except that the specific values of Mc, S, C, Y, N, X, and Me are different, as shown in Table 1.
[0098] Comparative Example 3 The preparation of the positive electrode slurry and positive electrode sheet of Comparative Example 3 is different from that of Example 1, and the rest is the same.
[0099] The positive electrode slurry of Comparative Example 3 was prepared by the existing wet method, and the preparation method is as follows: In a beaker, NMP (N-methylpyrrolidone) and polyvinylidene fluoride are fully mixed to form a glue solution, wherein the mass ratio of polyvinylidene fluoride to NMP is 2:67, carbon black is added and fully stirred and dispersed, and then lithium iron phosphate is added and fully mixed to obtain a positive electrode slurry, wherein the mass ratio of lithium iron phosphate, carbon black, and polyvinylidene fluoride is 97:2:2, and the solid content of the positive electrode slurry is 60%. The positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil, and dried, rolled, and cut to obtain a positive electrode sheet. The coating thickness of the positive electrode sheet in Comparative Example 3 is the same as the thickness of the positive electrode active material layer in Example 1.
[0100] The actual injection mass Me of the battery of Comparative Example 3 is 2.0 g.
[0101] Table 1
[0102] Battery performance test The batteries prepared in the above-mentioned embodiments and comparative examples were subjected to the following performance tests.
[0103] 1) Energy density test To test the quality of the battery, the formed battery was charged at a constant current of 0.1C. After being charged to 3.8V, constant voltage charging was performed with a cut-off current of 0.05C. After being fully charged, the battery was discharged at a constant current of 0.1C to 2.5V. The first discharge capacity of the battery was recorded to obtain the mass energy density of the battery.
[0104] 2) 25℃ cycle capacity retention rate At 25°C, the formed battery was charged at 1C constant current to 4.2V, then charged at constant voltage with a cut-off current of 0.05C. After fully charged, it was discharged at 1C constant current to 3.0V, and the first discharge capacity of the battery was recorded. 1 , the battery is charged and discharged at 1C / 1C cycle, after 200 cycles, record the battery C 200 Discharge capacity; Battery 25℃ cycle capacity retention rate = C 200 / C 1 ×100%.
[0105] 3) EIS impedance test: The fully charged battery was discharged to 50% SOC under 0.2C constant current conditions, and the EIS of the discharge state was tested using an electrochemical workstation.
[0106] 4) DCIR impedance test: The fully charged battery is discharged to 50% SOC using a 0.2C constant current, and the DCIR of the discharge state is tested using a 2C constant current discharge for 30s.
[0107] 5) Rate charge and discharge test: The battery was charged to a voltage of 3.8V using a 0.2C constant current and constant voltage, and discharged to a voltage of 2.5V using a 0.2C / 0.5C / 1C / 2C constant current, to obtain the capacity retention rate of the battery at different discharge rates.
[0108] The test results of 1)~4) are shown in Table 2. The test results of 5) are shown in Table 3.
[0109] Table 2
[0110] Table 3
[0111] It can be seen from Tables 1 and 2 that the actual mass Me of the electrolyte injected in Example 1 and Comparative Examples 1-2 does not satisfy the relationship In comparative example 1, the actual amount of electrolyte injected is small, the battery room temperature cycle capacity retention rate is low, the EIS test impedance increases, the DCIR is also large, and the rate performance is poor. It is speculated that due to the small amount of electrolyte injected, the electrode wettability is poor, the electrolyte ion conductivity is reduced, the battery internal resistance increases, and the cycle performance and rate performance are poor; Me in comparative example 2 is large, the battery energy density is low, the impedance increases, and the battery rate performance does not improve; it shows that excessive injection of electrolyte does not improve the battery cycle performance and rate performance, but also reduces the battery energy density and increases the impedance. By comparing Example 1 with Comparative Examples 1-2, it can be concluded that the mass Me of the electrolyte injected into the battery satisfies the relationship 1, Relationship 1: The electrolyte infiltrates the electrode well, and the electrolyte has high ion conductivity, which improves the battery's rate performance and room temperature cycle performance and reduces the battery impedance.
[0112] Comparison between Example 1 and Comparative Example 3 shows that compared with the existing wet method for preparing the positive electrode sheet, the semi-dry method provided in the present application is used to prepare the positive electrode, and the mass Me of the electrolyte injected into the battery is limited to satisfy the relationship 1, Equation 1 can increase battery energy density, reduce battery impedance, and improve rate performance.
[0113] The comparison between Example 1 and Examples 4-6 shows that by changing the value of the mass Me of the injected electrolyte, as long as the relationship 1 is satisfied, According to equation 1, the obtained batteries have high energy density, good rate performance and cycle performance, and low battery impedance.
[0114] In contrast to Examples 1-3, the content of the positive electrode active material in the positive electrode agglomerate material is changed, the mass proportion S of the positive electrode active material in the solid powder is in the range of 94-98%, the mass proportion N of the first organic solvent in the organic solvent is in the range of 70-90%, the solid content X of the positive electrode agglomerate material is ≥70%, Y is 2.5-5 g / Ah, C is in the range of 0.07-0.30 Ah / g, and Me satisfies the relationship 1, , all have the effect of improving battery cycle performance, rate performance, and reducing battery impedance.
[0115] Comparing Example 1 with Examples 7 and 8, the type of positive electrode active material is changed, and Me satisfies Relationship 1, , the correct battery still has good rate performance and cycle performance.
[0116] By comparing Example 1 with Examples 9 and 10, the type of the second organic solvent is changed. As long as the second organic solvent is selected from one of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, vinylene carbonate, fluoroethylene carbonate, and ethyl acetate, the semi-dry method can be used to prepare the positive electrode sheet; the obtained batteries all have the same effect.
[0117] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, it should be understood by those skilled in the art that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention.
Claims
1. A secondary battery, characterized in that: It comprises an electrode core and a shell, wherein the electrode core and electrolyte are arranged in the shell, the electrode core comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer is obtained by compounding a positive electrode mass material on at least one side surface of the positive electrode current collector; The electrolyte includes an organic solvent, the organic solvent includes a first organic solvent and a second organic solvent, the positive electrode active material layer includes a solid powder and the second organic solvent, and the solid powder includes a positive electrode active material; The mass Me of the electrolyte actually injected into the shell satisfies the relation 1: Relation 1; Wherein, Mc is the mass of the positive electrode active material in the positive electrode active material layer, in g; S is the mass proportion of the positive electrode active material in the solid powder, unit: %; C is the theoretical gram capacity of the positive electrode active material, in Ah / g; Y is the filling coefficient of the battery, in g / Ah; N is the mass proportion of the first organic solvent in the organic solvent; X is the solid content of the positive electrode pellet material, in %.
2. The secondary battery according to claim 1, characterized in that: S is 94%~98%; And / or, Y is 2.5~5g / Ah.
3. The secondary battery according to claim 1, characterized in that: N is 70%~90%; And / or, X ≥ 70%.
4. The secondary battery according to claim 1, characterized in that: C is 0.07~0.30Ah / g.
5. The secondary battery according to claim 1, characterized in that: The positive electrode active material includes at least one of a lithium-containing compound and a sodium-containing compound; The lithium-containing compound includes one or more of lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel cobalt manganese oxide, and lithium-rich manganese-based materials; The sodium-containing compound includes one or more of Prussian blue compounds, sodium transition metal oxides and polyanion compounds; The second organic solvent includes one or more of a carbonate solvent and ethyl acetate; The carbonate solvent includes one or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propylene carbonate, vinylene carbonate, and fluoroethylene carbonate; The first organic solvent includes one or more of nitrile solvents, carboxylate solvents, ether solvents, and carbonate solvents.
6. A method for preparing a secondary battery according to any one of claims 1 to 5, characterized in that: The following steps are involved: Obtaining the positive electrode sheet, the negative electrode sheet and the separator, and assembling the positive electrode sheet, the separator and the negative electrode sheet into a pole core; Placing the pole core in a shell, injecting electrolyte into the shell, and performing formation to obtain the battery; The mass Me of the injected electrolyte satisfies the relation 1: Relationship 1.
7. The method for preparing a secondary battery according to claim 6, characterized in that: Obtaining the positive electrode sheet comprises the following steps: Prepare a positive electrode mass material, and compound the positive electrode mass material onto at least one side surface of the positive electrode current collector, The method for preparing the positive electrode mass material comprises the following steps: The positive electrode active material and the positive electrode conductive agent are mixed evenly to obtain a dry powder precursor; Mixing the positive electrode binder and the second organic solvent uniformly to obtain a glue solution; The dry powder precursor is mixed with the glue solution to obtain the positive electrode mass material; The solid content X of the positive electrode mass material is ≥70%.
8. The method for preparing a secondary battery according to claim 7, characterized in that: The positive electrode conductive agent includes one or more of carbon black, acetylene black, Ketjen black, graphene microspheres, three-dimensional conductive metal organic frameworks, porous spherical carbon, conductive nanotubes, nanofibers, graphene, and graphite microsheets; And / or, the positive electrode binder includes one or more of polytetrafluoroethylene and its modified polymers, rubber, modified rubber, polyvinylidene fluoride, modified polyvinylidene fluoride, polyimide, modified polyimide, polypropylene, modified polypropylene, polyacrylic acid, modified polyacrylic acid, polyvinyl alcohol, modified polyvinyl alcohol, polyvinyl butyral, modified polyvinyl butyral and polyacrylonitrile and modified polyacrylonitrile.
9. The method for preparing a secondary battery according to claim 7, characterized in that: Compounding the positive electrode mass material on at least one side of the positive electrode current collector comprises the following steps: The positive electrode mass material is prepared by rolling or rolling to obtain a positive electrode active material layer, and the positive electrode active material layer is compounded with at least one side surface of the positive electrode current collector to obtain the positive electrode sheet.
10. The method for preparing a secondary battery according to claim 7, characterized in that: The mass ratio of the positive electrode active material, the positive electrode conductive agent and the positive electrode binder is (94~98): (1~3): (1~3); And / or, in the glue solution, the mass ratio of the positive electrode binder to the second organic solvent is (1-3): (30-40).
Citation Information
Patent Citations
Alkali metal flow battery, and preparation method and application thereof
CN102983369A
Preparation method of lithium-sulfur battery
CN107316980A
Positive electrode slurry dispersing agent, preparation method thereof, positive electrode slurry, positive electrode plate and secondary battery
CN118380586A
Cited By
Battery and preparation method thereof
CN122051393A